Biphasic tumor of uterine origin – a case report and literature review - Oberda, Jakub; Rudzińska, Anna; Ponikowski, Kacper; Gumółka, Paulina; Kowalczyk, Natalia; Kuchta, Eliza; Kowalczyk, Zuzanna; Kowalewski, Piotr; Jabłońska, Keli; Wiśniewska, Jolanta; Szklener, Katarzyna (Quality in Sport, 2026)
Background: Uterine carcinosarcoma represents a rare subtype of the primary tumors of the uterus, consisting of less than 5% of uterine neoplasms. The most common symptom is abnormal vaginal bleeding. Most frequently, this type of cancer occurs in women over the age of 70. Aim: The aim of the paper is to present the significance of early diagnosis and treatment of uterine carcinosarcoma and to compare treatment methods among patients with different stages of this type of cancer. Materials and methods: This paper presents a case report of a 56 yeras old patient who was admitted to the hospital due to postmenopausal bleeding. During examination, an echogenic heterogeneous tumor was spotted in the uterine cervix. The materials obtained during the uterine dilation and curettage (D&C) revealed sarcoma stromale. During the second admission, laparoscopic hysterectomy was performed. Histopathological analysis of the material recognised neoplasm as carcinosarcoma not otherwise specified (NOS). According to the decision made during consultation, the patient was qualified for chemotherapy (6 cycles), followed up with radiotherapy. Results: Uterine carcinosarcoma is characterized by its unique, bi-phasic structure, aggressive, high-grade character and poor prognosis, which all create diagnostic and therapeutic difficulties. Due to its rare occurrence, precise histopathological examination is crucial in the diagnostic process and further treatment administration. Conclusions: Carcinosarcoma is an uncommon and distinctive form of uterine tumor. Its unusual morphology can complicate the diagnostic process and histopathological evaluation, potentially delaying the final diagnosis. Furthermore, because of its biphasic nature, its treatment approach differs from that used for more typical uterine cancers.